wp 2020
DOI: 10.24149/wp2025
|View full text |Cite
|
Sign up to set email alerts
|

Oil Prices, Gasoline Prices and Inflation Expectations: A New Model and New Facts

Abstract: The conventional wisdom that inflation expectations respond to the level of the price of oil (or the price of gasoline) is based on testing the null hypothesis of a zero slope coefficient in a static single-equation regression model fit to aggregate data. Given that the regressor in this model is not stationary, the null distribution of the t-test statistic is nonstandard, invalidating the use of the normal approximation. Once the critical values are adjusted, these regressions provide no support for the conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The use of a partially identified model not only dispenses with the need for potentially controversial additional identifying assumptions, but also facilitates the construction of scenarios for the identified shock. Models ( 1) and ( 2) are an extension of a lower-dimensional model examined and validated in Kilian and Zhou (2021) who show that in their setting very similar results are obtained under a range of alternative, more restrictive identifying assumptions.…”
Section: Model Structurementioning
confidence: 80%
See 2 more Smart Citations
“…The use of a partially identified model not only dispenses with the need for potentially controversial additional identifying assumptions, but also facilitates the construction of scenarios for the identified shock. Models ( 1) and ( 2) are an extension of a lower-dimensional model examined and validated in Kilian and Zhou (2021) who show that in their setting very similar results are obtained under a range of alternative, more restrictive identifying assumptions.…”
Section: Model Structurementioning
confidence: 80%
“…This model recognizes that it is gasoline prices rather than the price of crude oil that enter the consumer basket and that the gasoline price is what matters for the determination of household inflation expectations because of its salience (see, e.g., Coibion and Gorodnichenko 2015;Binder 2018). The identification of the model builds on insights in Kilian and Zhou (2021), who show that a structural VAR model is a more natural framework to estimate the effect of gasoline price shocks on inflation and inflation expectations than reduced-form correlations. In this paper, we take the analysis a step further by discussing how scenarios about the future evolution of the price of crude oil (such as the scenario entertained by the Bank of America) may be econometrically evaluated within our structural VAR model, along with the impact of past gasoline price shocks on inflation and inflation expectations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis showed that gasoline price volatility accounts for approximately 39% of the variation in household inflation. Kilian and Zhou (2020) propose that more examination is needed to determine the causes of inflation in America as gas prices alone cannot give reasonable information on inflation rate volatility.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…the rationale of these restrictions and of the VAR model speci…cation can be found inKilian and Zhou (2020a) whose analysis in turn is motivated byCoibion and Gorodnichenko (2015). The model is estimated based on a conventional uniform-Gaussian-inverse Wishart prior with the prior means of all slope parameters set to zero.…”
mentioning
confidence: 99%